Effect of Resistance Training Under Normobaric Hypoxia on Physical Performance, Hematological Parameters, and Body Composition in Young and Older People - Törpel, Alexander; Peter, Beate; Schega, Lutz (Frontiers in Physiology, 2020)
Background: Resistance training (RT) under hypoxic conditions has been used to increase muscular performance under normoxic conditions in young people. However, the effects of RT and thus of RT under hypoxia (RTH) could also be valuable for parameters of physical capacity and body composition across the lifespan. Therefore, we compared the effects of low- to moderate-load RTH with matched designed RT on muscular strength capacity, cardiopulmonary capacity, hematological adaptation, and body composition in young vs. older people. Methods: In a pre-post randomized, blinded, and controlled experiment, 42 young (18 to 30 yr) and 42 older (60 to 75 yr) participants were randomly assigned to RTH or RT (four groups: RTH young, RT young, RTH old, RT old). Both groups performed eight resistance exercises (25-40% of 1RM, 3x15 repetitions) four times a week over five weeks. The intensity of hypoxic air for the RTH was administered individually in regard to the oxygen saturation of the blood (SpO2): 80-85. Changes and differences in maximal isokinetic strength, cardiopulmonary capacity, total hemoglobin mass (tHb), blood volume (BV), fat free mass (FFM), and fat mass (FM) were determined pre-post, and the acute reaction of erythropoietin (EPO) was tested during the intervention. Results: In all parameters, no significant pre-post differences in mean changes (p=.120 to 1.000) were found for all four groups. However, within the four groups, isolated significant improvements (p<.050) of the single groups were observed regarding the muscular strength of the legs and the cardiopulmonary capacity. Discussion: Although the hypoxic dose and the exercise variables of the RT were based on the current recommendations of RTH, the RTH design used had no superior effect on the tested parameters in young and older people in comparison to the matched designed RT under normoxia after a five-week intervention period. Based on previous RTH-studies as well as the knowledge about RT in general, it can be assumed that the expected higher effects of RTH can may be achieved by changing exercise variables (e.g., longer intervention period, higher loads).